Trapa natans Husk‐Derived Nanoporous Carbons as Electrode Materials for Sustainable High‐Power Microbial Fuel Cell Supercapacitor Systems. Issue 5 (6th May 2022) - Hsu, Chia-Chieh; Lin, Yi-Chu; Lin, Yao-Yu; Li, Hsin-Tien; Ni, Chung-Sheng; Liu, Chao-I; Chang, Chao-Chin; Lin, Liang-Chen; Pan, Yung-Tin; Liu, Shih-Fu; Liu, Tzu-Yin; Chen, Han-Yi
Abstract : Energy, Sustainability, and Climate Change In article number 2100163 by Tzu‐Yin Liu, Han‐Yi Chen, and co‐workers, a Trapa natans husks‐derived electrode material (TNH) is used in microbial fuel cells (MFCs) with a high average power density of 5713 mW m −2 . Moreover, supercapacitors (SCs) with TNH‐based electrodes are used as energy storage from MFCs, exhibiting a high specific capacitance of 85 F g −1 after 1000 cycles. It is shown that TNH is a promising material in MFC‐SC system.